Elucidating the function of the retropepsin APRc as a moonlighting immune evasion factor of Rickettsia - Matos, Ana Luísa Abrantes de (2022)
Dissertação de Mestrado em Biologia Celular e Molecular apresentada à Faculdade de Ciências e Tecnologia